California State University, Hayward University Catalog 1978-1979 - California State University, Hayward:::::: (1978)
A catalog of courses offered by California State University, Hayward for the academic year 1978-1979. Includes academic calendar, history of the college, names of faculty and administrators, and descriptions of courses and degrees offered.